Sampul, Daftar Isi, dan Pengantar Editor – Vol. 14 No. 2 (2025) - Alief Budiyono (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
Raushan Fikr Journal Volume 14, No. 2 (2025) presents twenty-one scholarly contributions that exemplify the evolving landscape of contemporary Islamic studies. The articles span five domains—social-religious studies, Islamic education, Islamic economy, theology and thought, and Islamic law—each addressing critical intersections of faith, society, and practice. Studies in the social-religious section engage themes of conflict resolution, halal certification in community markets, democratic citizenship, local resilience, and spiritual care for the elderly. Contributions to Islamic education highlight innovative pedagogical approaches, including digital games, problem-based learning, and creative classroom integration. The Islamic economy section offers analyses of financial ethics, marketing innovation, risk management, public service quality, agribusiness, and the global modest fashion industry. In theology, comparative reflections revisit liberationist thought and reimagine mahabbah across classical traditions. The legal dimension examines governance through Islamic principles of amanah, ‘adalah, and maslahah. Collectively, this volume underscores the journal’s commitment to rigorous, interdisciplinary, and socially relevant scholarship.